2018
DOI: 10.4172/2167-0420.1000445
|View full text |Cite
|
Sign up to set email alerts
|

Preconception Care Utilization and its Associated Factors among Pregnant Women in Adet, North-Western Ethiopia (Implication of Reproductive Health)

Abstract: Introduction: Preconception care is the entire ranges of measures to promote the health of the expectant mother and her child which includes health promotion and detecting pre-existing condition. Despite preconception care has different advantages on improving maternal and child health, utilization of preconception care utilization in developing countries is very low. Moreover; preconception care utilization by childbearing age group women in Ethiopia is not known or far too low. So, this study was aimed to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(45 citation statements)
references
References 19 publications
6
33
4
Order By: Relevance
“…Regarding geographical distribution of studies, four studies were from Oromia (30.7%) [ 16 , 18 , 23 , 27 ], four from Amhara (30.7%) [ 15 , 22 , 25 , 26 ], two from Tigray (15.4%) [ 21 , 24 ], two from (15.4%) SNNP[ 17 , 20 ] and one from AA (7.8%) [ 19 ]. Eleven of the included studies reported on knowledge[ 15 25 ], and six provided data on utilization of PCC[ 16 , 18 , 22 , 24 , 26 , 27 ] (Table 1 ). Once more, out of the thirteen included studies, eight had a quality score of eight, and the remaining five had a quality score of seven.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding geographical distribution of studies, four studies were from Oromia (30.7%) [ 16 , 18 , 23 , 27 ], four from Amhara (30.7%) [ 15 , 22 , 25 , 26 ], two from Tigray (15.4%) [ 21 , 24 ], two from (15.4%) SNNP[ 17 , 20 ] and one from AA (7.8%) [ 19 ]. Eleven of the included studies reported on knowledge[ 15 25 ], and six provided data on utilization of PCC[ 16 , 18 , 22 , 24 , 26 , 27 ] (Table 1 ). Once more, out of the thirteen included studies, eight had a quality score of eight, and the remaining five had a quality score of seven.…”
Section: Resultsmentioning
confidence: 99%
“…This study showed that the utilisation of PCC among women in Ethiopia was significantly associated with age (> 30 years) and knowledge of PCC. According to this meta-analysis, two primary studies identified that older age (> 30 years) was significantly associated with the utilisation of PCC [ 22 , 26 ]. Those women who were older (> 30 years) were approximately two and a half times (OR = 2.43, 95%CI, 1.30–4.53) higher concerning utilising PCC compared to their counterparts.…”
Section: Resultsmentioning
confidence: 99%
“…There was not only lack of knowledge about PCC among women with diabetes mellitus, hypertension and obesity but there was also lack on intent for pre-conception health promotion and pregnancy planning among women in Hershey, United States [16]. About 15% women were aware about preconception folic acid supplementation in North-western Ethiopia [29]. Highest knowledge was in the area of RCH risk factors had and lowest about health promotion [26].…”
Section: Preconception Services: Knowledge and Utilizationmentioning
confidence: 99%
“…Knowledge on PCC is usually found to be associated with education, age of the woman, number of children, family planning measures, receipt of information, chronic health problems and monthly income in Zambia, Northwest Ethiopia and Nepal [10,25,29,31].…”
Section: Preconception Services: Knowledge and Utilizationmentioning
confidence: 99%
“…For example, in France (15.8%) [ 16 ], data from the Maryland Pregnancy Risk Assessment Monitoring System (13.5%) [ 17 ], Brazil (15.9%) [ 18 ], Iran (31.7%) [ 19 ], Southern Sri Lanka (27.2%) [ 20 ] and Nigeria (2.5%) [ 21 ]. In Ethiopia, despite the existence of different opportunities (health extension programs, expansion of health facilities along with human resources, linkage among health facilities, and the existence of community-based health insurance), little is known about PC, and the existing data showed that utilization of PC was very low [ 22 24 ]. Therefore, this study aimed to explore barriers to the uptake of preconception care from the perspectives of consumers and providers in the selected district, which helps to inform future interventions for increasing utilization of preconception care.…”
Section: Introductionmentioning
confidence: 99%